2007
DOI: 10.1051/0004-6361:20065867
|View full text |Cite
|
Sign up to set email alerts
|

Abundance analysis of barium and mild barium stars

Abstract: Aims. We compare and discuss abundances and trends in normal giants, mild barium, and barium stars, searching for differences and similarities between barium and mild barium stars that could help shed some light on the origin of these similar objects. Also, we search for nucleosynthetic effects possibly related to the s-process that were observed in the literature for elements like Cu in other types of s-process enriched stars. Methods. High signal to noise, high resolution spectra were obtained for a sample o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(104 citation statements)
references
References 52 publications
(99 reference statements)
8
91
4
Order By: Relevance
“…ζ Cap and ζ Cyg. These stars were analysed by Smiljanic et al (2007). The agreement between the two studies on the s-process abundances is reasonable (in particular, both studies find large overabundances in ζ Cap and much milder ones in ζ Cyg), except for Sr in ζ Cap: Smiljanic et al (2007) Berdyugina (1994), Zacs et al (1997), and Barisevičius et al (2010) concluded, like we do, that DR Dra does not exhibit any s-process overabundance.…”
Section: Comparison With Previous Studiessupporting
confidence: 84%
“…ζ Cap and ζ Cyg. These stars were analysed by Smiljanic et al (2007). The agreement between the two studies on the s-process abundances is reasonable (in particular, both studies find large overabundances in ζ Cap and much milder ones in ζ Cyg), except for Sr in ζ Cap: Smiljanic et al (2007) Berdyugina (1994), Zacs et al (1997), and Barisevičius et al (2010) concluded, like we do, that DR Dra does not exhibit any s-process overabundance.…”
Section: Comparison With Previous Studiessupporting
confidence: 84%
“…The stellar sample targeted in our study includes eight mild and classical barium stars and six normal giants of Smiljanic et al (2007), with a spectral S /N ratio ranging from 200 to 450 in the visible range. Smiljanic et al (2007) determined T eff , log g, and the metallicities from the simultaneous excitation and ionization equilibria of the equivalent widths of an average number of 120 Fe i and 12 Fe ii lines. Surface gravities were also computed from the stellar luminosities and theoretical HR diagrams, and a very good agreement was found for the two sets of gravities.…”
Section: Observations and Atmospheric Parametersmentioning
confidence: 99%
“…A summary of the stellar parameters is given in Table 1. The reader is referred to Smiljanic et al (2007) for a journal of the observations, details of derivation of atmospheric parameters, and the respective uncertainties.…”
Section: Observations and Atmospheric Parametersmentioning
confidence: 99%
See 2 more Smart Citations